Analysis of the Design of a Decision-Making System for Assessing Employees and Clothing Products using the Simple Additive Weight Method Web-Based - Muhammad Subhana; Santa Margita (Komunitas Dosen Indonesia, 2021)
Indonesia is a country that is currently developing in technology and internet networks that follow modern times so that people can easily access and explore information needs when people need something, for that several companies and traders have now invested in a web-based program and mobile so that the public can easily access the company's web regarding marketing information on what products are being sold and can compare them to other products, one of which is the Indonesian market place which currently spoils the community in terms of primary, secondary and tertiary needs, DNA.GALERI Boutique is a boutique that is engaged in Muslim clothing products for young women in dynamic and elegant designs adapting to changing times, attracting Muslim women to love to cover their limbs fully in avoiding aurat. Because of the important role of employees, and the development of employees who work with each other and do not know the quality of the employees when selling and serving goods to the maximum or not, employee assessment is needed to measure how productive the work done in selling goods for sales turnover is. Likewise, for products being marketed, it is necessary to measure transparency assessment that has been assessed by the community, which will later be known to the boutique owner which product is the best and make the product worthy of being an option to add stock or be used as a sampling in design developments that will attract public attention. For this reason, a system design was made to support and produce a decision in assessing good employees and assessing superior clothing products from other models of clothing using the SAW method supported by web-based technology in assessing employees and boutique products sold